Inspection of supersonic flows in a CD nozzle using experimental method - Azami, Muhammad Hanafi; Faheem, Mohammed; Aabid, Abdul; Mokashi, Imran; Khan, Sher Afghan (2019)
In high speed flows nozzles are used to change pressure energy to kinetic energy which in turn is used to produce thrust. In a converging-diverging nozzle, flow is augmented from subsonic to sonic velocity at the throat and further expanded to supersonic velocities at the exit. In this paper, an experimental study is performed to evaluate the supersonic flow in a CD nozzle with a suddenly expanded duct. At the base of the nozzle, the base pressure is controlled by employing tiny jets of 1 mm diameter with a circular cross-section having exit Mach number of as unity are arranged at ninety degrees at a PCD of 13 mm and 6.5 mm from the central jet axis. Obtained wall pressure distribution is shown for Mach number 2.8, and Axi-symmetric round brass duct was used to join micro-jets, an area ratio of that duct is 3.24. Tests were conducted for L/D from 10 to 1, and the level of expansion for tests considered for wall pressure data acquisition was from 3, 5, 7, 9 and 11. The results indicate that the flow field was not aggravated due to the deployment of the control.